E-diasporas Atlas. Exploration and Cartography of Diasporas in the Digital Network - Diana Dumitriu (Romanian Journal of Communications and Public Relations, 2023)
The symbolic imperialism of internet, which ended up covering every aspect of our life, whether public or private, meant also a redefining process in terms of social space, social time and social relationships. Moreover, it contributed as a significant platform and amplifier resort to the consolidation of the ‘network society’ (Castelles, 1996) and its expansion to the virtual level. Each component of the social dynamics found its corollary and, in many cases, its substitute in the ‘e’-reality generated by the new technologies and, therefore, we now speak of e-democracy, e-learning, e-culture etc.